The role of small business in forming the creative economy in Ukraine - L.M.; A.V. (Економіка, управління та адміністрування, 2023)
This article explores the role of small business in the formation of a creative economy in Ukraine. An important task of any economy is to ensure rapid economic growth, which is not possible without the use of entrepreneurial innovations. It was determined that the main advantages of small business are the ability to quickly respond to changes in the market, greater flexibility in decision-making and the ability to innovate. The growth of the creative economy is closely related to the creation of a favorable business environment within the country, which is a key factor in increasing the competitiveness of the national economy. In the conditions of European integration, the development of human potential, entrepreneurship and innovation in the context of the development of creative industries can ensure increased competitiveness of the Ukrainian economy, as well as long-term economic growth and innovative development of enterprises. The creative economy by its very nature is a fusion of commercial processes and human capital with an emphasis on creativity and non-standard thinking. This partnership generates innovative ideas and solutions. However, companies face various challenges such as market saturation, competition and changing consumer demands. The success of a business depends on its ability to adapt and remain competitive in the face of these obstacles. The article highlights the advantages of small business, the factors affecting economic development, the challenges of the formation of small business and the creative economy, as well as the role of small business and the creative economy during conflicts. The main problems affecting the formation of the business environment and the functioning of large, medium and small enterprises are identified, namely: tax burden, in particular administrative burdens; corruption of state institutions; problems of the judicial system and weak protection of property rights; insufficient number of qualified personnel; lack of working capital and problems in logistical connections. A number of measures are proposed for the effective formation of a favorable business environment and the development of creative industries.